2016
DOI: 10.12688/f1000research.8657.2
|View full text |Cite
|
Sign up to set email alerts
|

Priority regions for research on dryland cereals and legumes

Abstract: Dryland cereals and legumes  are important crops in farming systems across the world.  Yet they are frequently neglected among the priorities for international agricultural research and development, often due to lack of information on their magnitude and extent. Given what we know about the global distribution of dryland cereals and legumes, what regions should be high priority for research and development to improve livelihoods and food security? This research evaluated the geographic dimensions of these crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There are more than 160 million hectares of dryland cereal and legume crops worldwide. The regions where these crops are grown are prone to drought and heat stress, have limiting soil constraints, contain half of the global population, and account for 60% of the planet’s poor and malnourished people ( Hyman et al, 2016 ). A recent study involving six major crop commodity groups in 131 countries reported losses from 1961–2014 of 1.6% in cereal production, 0.5% in oil crops, 0.6% in pulses, 0.2% in fruits, and 0.09% in vegetables due to drought and heat disasters.…”
Section: Introductionmentioning
confidence: 99%
“…There are more than 160 million hectares of dryland cereal and legume crops worldwide. The regions where these crops are grown are prone to drought and heat stress, have limiting soil constraints, contain half of the global population, and account for 60% of the planet’s poor and malnourished people ( Hyman et al, 2016 ). A recent study involving six major crop commodity groups in 131 countries reported losses from 1961–2014 of 1.6% in cereal production, 0.5% in oil crops, 0.6% in pulses, 0.2% in fruits, and 0.09% in vegetables due to drought and heat disasters.…”
Section: Introductionmentioning
confidence: 99%
“…Agronomic data can also be used as a benchmark in yield gap studies for what farmers might be able to achieve under improved conditions and management ( Gustafson et al , 2014 ). Trial data collected across a large geographic extent and over decades can be useful to monitor climate change or the spread of pests and diseases ( Gourdji et al , 2012 ; Lampe et al , 2014 ; Lobell et al , 2011 ), to understand the drivers of technology adoption, to set research and development priorities and to conduct both ex-ante and ex-post impact analysis ( Badu-Apraku et al , 2011 ; Hyman et al , 2016 ; Renkow & Byerlee, 2010 ; Setimela et al , 2005 ). One of the most obvious uses of agricultural trial data is to calibrate crop models, for a single location or for spatially explicit models covering countries, regions or the entire globe.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may emphasize the role of powerful membrane proteins in strengthening domestic lines by a composite stability (resilience, temperature and metabolic) when compared to international common bean specimens under investigation [7]. Following research on domestic bean collection in terms of the application of another developing branches of bean biology and biotechnology is considered to require special attention of researchers and authorities in charge [8].…”
mentioning
confidence: 99%